The analysis of deformation states high strength fibre-reinforced concrete plates in flexural - Smarzewski, Piotr; Szwaj, Mariusz; Szewczak, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article presents the results of bending tests on reinforced concrete made of high strength concrete with water/(cement+microsilica) ratio of 0.2 with addition of steel and polypropylene fibres obtained with the system of non-contact three-dimensional displacement measuring system – ARAMIS. The plates were reinforced with grids and the variable was the content of fibres in concrete. The experiments proved significant influence of structural reinforcing combinations on load capacity of plates.